PERANAN ORGANISASI KEMAHASISWAAN DALAM PENGEMBANGAN CIVIC SKILLS MAHASISWA - Kosasih, Kosasih (Universitas Pendidikan Indonesia, 2016)
The organisation of student of university holds the big role in developing studentsâ€™civic skills to preprare themselves into civilization. Based on the result of the observation and discussion, found that: studentsâ€™ motivation for â€œormawaâ€ is decreasing because of they are more intended on academic area and dealt with the competition of life style which comes closer to the hedonism than to civilization. University studentsâ€™ organisation is using many kinds of media for socialize. An effective media will make an easier way in receiving an information, also it can spread out the information which is related to many kinds of activities that is done by â€œormawaâ€quickly and accurately. The role of â€œormawaâ€ towards skill development of the society of the students of university is as the place of student aspiration and as a trigger of university studentsâ€™ ways of think for critically thinking, taking responsibe, and scientifically. The problems which â€œormawaâ€ lives during the activity especially in civic skills development are about internal and external problems. For instance, about finance, legalization, life style, communication and coordination, studentsâ€™ motivation, the difference of studentsâ€™ background, facility, and administration. The attempt to solve these problems are by doing develoving culture, designing program and an attractive material, discipline, comprehendingconflict management, providing working assessment or evaluation, and doing ormawaâ€™s role in university as well as possible.Keyword: Students, university students organisation, civic skill